CO2 absorption performance enhancement by dodecane nanoemulsion absorbents. (March 2019) - Kim, Seonggon; Xu, Ronghuan; Lee, Wonhyeok; Choi, Chang Kyoung; Kang, Yong Tae
Highlights: Nanoemulsion absorbents are manufactured by dispersing nano-sized dodecane in methanol. Span 60 and Tween 60 are mixed at a ratio of 4:6 as a surfactant. A nanoemulsion absorbent with a dodecane concentration of 0.05 vol% shows the best absorption performance. CO2 absorption performance is enhanced as high as 10% by the nanoemulsion absorbent. New CO2 absorption enhancement mechanisms are proposed. Abstract: Among the CO2 capture technologies, the physical absorption is one of the most common absorption methods. However, the physical absorption process is operated at extremely low temperature, and therefore huge freezing energy is required. The objective of this study is to develop the nanoemulsion absorbents that can be operated at room temperature. The nanoemulsion absorbents are prepared by the ultrasonication method. Based on the chemical properties, Span 60 and Tween 60 are added to maintain a good dispersion stability. CO2 absorption experiments using a porous nozzle absorber are conducted for various dodecane concentration (0.005–0.5 vol%) and CO2 flow rate (0.06–0.12 g/s). It is found that the CO2 absorption performance of 0.05 vol% nanoemulsion absorbents is 10% higher than that of pure methanol. Through the single CO2 bubble absorption visualization experiments, it is confirmed that the nanoemulsion absorbents cause faster bubble absorption than pure methanol does. The turbidity index (Nephelometry turbidity unit) of nanoemulsion absorbents is kept constant for seven days, which means a good dispersion stability. The enhancement mechanism of CO2 absorption is explained based on the Einstein-Stokes' equation, cryogenic transmission electron images, and droplet size measurements. The key idea is that nano-sized dodecane (64 nm) absorbs the CO2 molecules and transports it to the bulk region by the Brownian diffusion. A random walk model is used to investigate the droplet size prediction and CO2 absorption performance enhancement.